Varenicline Treatment for Waterpipe Smoking Cessation. Issue 1 (5th July 2022) - Chami, Hassan A; Zaouk, Nour; Makki, Maha; Tamim, Hani; Shaya, Monique; Talih, Farid
Abstract: Background: Waterpipe smoking is increasing worldwide with no proven interventions for cessation. We compared abstinence rates with 12-week varenicline therapy versus placebo among habitual waterpipe smokers willing to quit. Methods: This double-blind placebo-controlled single-center trial, randomized waterpipe smokers from Lebanon who did not smoke other tobacco products to receive varenicline or placebo for 12 weeks. All participants also received three structured 30-minute individual behavioral intervention sessions. The primary outcome was repeated point prevalence abstinence assessed by self-report and verified by exhaled carbon monoxide three times during 12 weeks and analyzed with the intention to treat. End of treatment urine cotinine, weight, blood pressure, anxiety, depression, withdrawal, and adverse symptoms were also assessed. Results: In total, 152 waterpipe smokers (mean age 38 years [SD = 13], 39% females) willing to quit, who smoked waterpipe exclusively (average 2.3 per day [SD = 1.6] for 16.8 years [SD = 10.8]) were randomized. Seventy-nine participants (52%) with any missing abstinence assessment were considered to have relapsed. Repeat point prevalence abstinence rate was numerically higher among the varenicline group compared to placebo, but the difference did not reach statistical significance when assessed by self-report (16.9 vs. 13.6%, respectively, p = .6) and when further verified by exhaled carbon monoxide (14.1% vs. 9.9%, respectively, p = .4). Abstinence rates were similar in both groups when further verified by urine cotinine at end of treatment. No serious adverse events were reported, adverse symptoms and other outcomes were similar in the varenicline and placebo arms. Conclusions: Varenicline for 12 weeks was not more effective than placebo to achieve abstinence among daily waterpipe smokers. Implications: Varenicline in combination with a behavioral intervention did not significantly enhance the quit rate among exclusive waterpipe smokers compared to behavioral intervention plus placebo. We experienced difficulty enrolling exclusive waterpipe smokers willing to quit and observed high dropout rates among participants demonstrating the difficulties of waterpipe smoking cessation.